ASL Wiki: An Exploratory Interface for Crowdsourcing ASL Translations - Glasser, Abraham; Minakov, Fyodor; Bragg, Danielle (ASSETS 2022, 2022)
The Deaf and Hard-of-hearing (DHH) community faces a lack of information in American Sign Language (ASL) and other signed languages. Most informational resources are text-based (e.g. books, encyclopedias, newspapers, magazines, etc.). Because DHH signers typically prefer ASL and are often less fluent in written English, text is often insufficient. At the same time, there is also a lack of large continuous sign language datasets from representative signers, which are essential to advancing sign language research and technology. In this work, we explore the possibility of crowdsourcing English-to-ASL translations to help address these barriers. To do this, we present a novel bilingual interface that enables the community to both contribute and consume translations. To shed light on the user experience with such an interface, we present a user study with 19 participants using the interface to both generate and consume content. To better understand the potential impact of the interface on translation quality, we also present a preliminary translation quality analysis. Our results suggest that DHH community members find real-world value in the interface, that the quality of translations is comparable to those created with state-of-the-art setups, and shed light on future research avenues.